Synthetic and Mechanistic Studies Related to Oxadiazolines and Azomethine Imine Ylids - Ramakrishnan, Kottieth (My University, 1975)
Several new oxadiazolines have been synthesized by the cyclization of mixed carbohydrazones derived from aromatic aldehydes and aliphatic ketones. A mechanism for the cyclization is discussed on the basis of the regiospecificity observed in these reactions. Pyrolysis of these oxadiazolines led to the synthesis of a number of azomethine imine ylids, which could not be made by the only other existing route. The mechanism of this pyrolytic process was investigated by trapping experiments and spectroscopic methods and the intermediacy of an N-isocyanatoimine was established. Structures of the products formed by the trapping experiments were also determined.
Keywords: Chemistry; Chemistry